2017
DOI: 10.1186/s13023-017-0583-7
|View full text |Cite
|
Sign up to set email alerts
|

Early disease progression of Hurler syndrome

Abstract: BackgroundNewborn screening for mucopolysaccharidosis type I (MPS I) shows promise to improve outcomes by facilitating early diagnosis and treatment. However, diagnostic tests for MPS I are of limited value in predicting whether a child will develop severe central nervous system disease associated with Hurler syndrome, or minimal or no central nervous system involvement associated with the attenuated phenotypes (Hurler–Scheie and Scheie syndromes). Given that the optimal treatment differs between Hurler syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 25 publications
3
63
0
1
Order By: Relevance
“…The median head circumference for untreated individuals with severe MPS I is well above the CDC reference curves by 3–4 months of age through 3 years of age. Previous studies have shown that individuals with untreated severe MPS I have head circumferences larger than population norms, but less is known about the attenuated phenotype (Aldenhoven et al, ; Kiely, Kohler, Coletti, Poe, & Escolar, ; Tylki‐Szymanska, Rozdzynska, Jurecka, Marucha, & Czartoryska, ). An analysis of 55 individuals with severe MPS I from a single center reported that enlarged head circumference was apparent at a median age of 8 months (Kiely et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The median head circumference for untreated individuals with severe MPS I is well above the CDC reference curves by 3–4 months of age through 3 years of age. Previous studies have shown that individuals with untreated severe MPS I have head circumferences larger than population norms, but less is known about the attenuated phenotype (Aldenhoven et al, ; Kiely, Kohler, Coletti, Poe, & Escolar, ; Tylki‐Szymanska, Rozdzynska, Jurecka, Marucha, & Czartoryska, ). An analysis of 55 individuals with severe MPS I from a single center reported that enlarged head circumference was apparent at a median age of 8 months (Kiely et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that individuals with untreated severe MPS I have head circumferences larger than population norms, but less is known about the attenuated phenotype (Aldenhoven et al, ; Kiely, Kohler, Coletti, Poe, & Escolar, ; Tylki‐Szymanska, Rozdzynska, Jurecka, Marucha, & Czartoryska, ). An analysis of 55 individuals with severe MPS I from a single center reported that enlarged head circumference was apparent at a median age of 8 months (Kiely et al, ). Thus, higher‐than‐normal OFC can serve as a clue to the diagnosis of MPS I, similar to males with MPS II (Parini, Jones, Harmatz, Giugliani, & Mendelsohn, ).…”
Section: Discussionmentioning
confidence: 99%
“…Hearing loss, conductive, sensorineural and mixed, is very frequent in MPSs, has early onset and is progressive [48,86,[147][148][149]. No data on the impact of ERT on hearing function is available in the clinical trials nor in the open label extension studies [17][18][19]22,[36][37][38].…”
Section: Hearingmentioning
confidence: 99%
“…Early diagnosis of MPS I allows an approach of intravenous enzyme replacement therapy (Iduronidase sold as Aldurazyme (Genzyme)), which provides stabilization of the clinical symptomatology [132]. Another therapeutic approach is hematopoietic stem cell transplantation.…”
Section: Mps I (Hurler Syndrome)mentioning
confidence: 99%